(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2025)
This article examines the key risks and threats of falling into poverty among the employed population. Based on an analysis of socioeconomic factors, the causes of working poverty are identified and public policy directions for reducing this phenomenon are proposed. The problem of working poverty requires a comprehensive approach, including political and economic measures aimed at increasing economic mobility, timely indexation of the minimum wage, training and retraining.